The spectrum of defect ABJM theory - Charlotte Kristjansen; Xin Qian; Chenliang Su (Journal of High Energy Physics)
Abstract We determine the spectrum of quantum fluctuations in a 1 2 $$ \frac{1}{2} $$ -BPS domain wall version of ABJM theory, thereby enabling the perturbative exploration of the corresponding defect CFT. As expected, the spectrum reflects the supersymmetry of the model.